A standard model of optimum resource allocation for local authorities - Atan, Ruhaya; Sawiran, Mohd Sahar; Abdul Rahman, Suryani; Mohamed, Nafsiah; Mail, Rasid; Kamarudin, Norbaizura (2011)
Local authorities play an important role in the management of towns and cities in urban societies. Normally, they provide services like providing better amenities, cleanliness in building and premises, good transportation system, licensing of commercial activities, garbage collection as well as approving architectural plans for development. The objective is to ensure peaceful and conducive living for the populace. However, in Malaysia, the past decade saw the emergence of somewhat poor management of some local authorities, which led them to uncontrolled indebtedness. This study attempts to determine the financial trends and investigate the public perception of local authorities in Selangor and tries to adopt a model, which gives optimum allocation of resources within the local authorities.